Fully Coupled Modeling of Athlete Force Application and Power Transfer in Rowing Ergometry - Stephen Tullis; Cameron Galipeau (Proceedings, 2020)
A fully coupled model of an athlete’s muscular force output combined with a load resistance is developed and investigated in context of ergometer rowing. The athlete force is based on a simple Hill equation hyperbolic-in-speed, and parabolic-in-length model. Coupling this force function with the dynamics of the ergometer load and inertia and athlete’s own body mass inertia produces a trajectory of the resultant motion in force-speed-length space. The coupled equations were solved using a first order time-marching procedure, and iteratively calculated starting conditions based on ergometer spin-down during the recovery period between strokes. The results agree well with experimental measurements available from Kleshnev particularly given the relatively simple, and untuned, athlete force model used. Changing the load resistance changed the trajectory of the stroke, with qualitative agreement with the expected outcomes.